PERKEMBANGAN PENDIDIKAN INKLUSIF DI INDONESIA - Zein Damanik, Muhammad; Hayati Siahaan, Mala; Murniati Damanik, Sri (Sekolah Tinggi Ilmu Tarbiyah Al-Bukhary Labuhanbatu, 2024)
This journal reviews the development of inclusive education in Indonesia. This research aims to explain the history of inclusive education in schools in Indonesia to its development in education today. This research uses qualitative methods with literature studies that take reliable sources or references from several books. The activities carried out in this research were collecting library data, reading and taking notes, and managing research materials in accordance with the existing problem. The explanation in this journal contains the meaning of inclusive education, the history of inclusive education in Indonesia and an explanation of how inclusive education developed in Indonesia.